2011 IEEE International Conference on Computer Applications and Industrial Electronics (ICCAIE) 2011
DOI: 10.1109/iccaie.2011.6162183
|View full text |Cite
|
Sign up to set email alerts
|

Approach of a UML profile for Berkeley Open Infrastructure for network computing (BOINC)

Abstract: Despite the current enormous hype and popularity of Grid Computing environments like Amazons EC2 or Microsoft's Windows Azure , there exist open-source and free of cost software frameworks which allow to create high performance computing installation by means of Public Resource Computing (PRC). One PRC framework is BOINC (Berkeley Open Infrastructure for Network Computing) for solving large scale and complex computational problems. Each computer works on its own workunits independently from each other and send… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It has been successfully demonstrated that it is possible to run simulations of a climatic model using infrastructure in the cloud; while this might not seem complex, to the best of our knowledge, it has never previously been tested. This efficient use of MTC resources for scientific computing has previously been used to facilitate real research in other areas (Añel et al, 2014;Schaller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been successfully demonstrated that it is possible to run simulations of a climatic model using infrastructure in the cloud; while this might not seem complex, to the best of our knowledge, it has never previously been tested. This efficient use of MTC resources for scientific computing has previously been used to facilitate real research in other areas (Añel et al, 2014;Schaller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A middleware is needed for task and data distribution. Volunteer computing was made possible only after the development of middleware systems such as JXTA, XtremeWeb, and Berkeley Open Infrastructure for Network Computing (BOINC) . BOINC was initially designed for PCs but was later in 2014 extended for mobile devices.…”
Section: Related Workmentioning
confidence: 99%
“…We have discussed various MCC frameworks: (1) commercial clouds with complete task offloading for mobile devices, (2) commercial clouds with partial task offloading for mobile devices, (3) volunteer global cloud with stationary devices, (4) volunteer global cloud with mobile devices, (5) commercial or volunteer global cloud with mobile devices using cloudlets, and (6) volunteer local cloud with mobile devices …”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not the aim of this paper to describe the internals of BOINC, and for better comprehension of the problem that we are trying to solve, it is recommended to review previous works about this knowledge, such as Ries et al (2011).…”
Section: Introductionmentioning
confidence: 99%